Responsibility-Shifting through Delegation: Evidence from China's One-Child Policy - Yiming Liu; Yi Han (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
We provide evidence on how responsibility-shifting through delegation occurred in China's implementation of the one-child policy. We show that trust in local governments was reduced when they were the primary enforcer of the policy (1979–1990), while trust in neighbors was reduced when civilians were incentivized to report neighbors' violations of the policy to the authorities (1991–2015). This effect was more pronounced among parents of a firstborn daughter, who were more likely to violate the policy due to the deep-rooted son preference. This study provides the first set of field evidence on the responsibility-shifting effect of delegation.
Keywords: D02; D04; D90; J18; 330; delegation; responsibility-shifting; One-Child policy